Enhancing maize drought and heat tolerance: single vs combined plant growth promoting rhizobacterial inoculation - Notununu, Iviwe; Moleleki, Lucy; Roopnarain, Ashira; Adeleke, Rasheed (Frontiers in Plant Science, 2024)
Maize (Zea mays L.) is an important staple crop in Sub-Saharan Africa and is known for its susceptibility to concurrent drought and heat stress. The use of plant growth-promoting rhizobacteria (PGPR) as biofertilizers is thought to contribute to the adaptation and survival of plants under these abiotic stresses. Towards this end, this study aimed to identify drought and heat tolerant PGPR isolates and evaluate their potential to mitigate the effects of concurrent drought and heat stress on the early growth of maize. The study also identified the expression of the genes in maize that are responsive to heat and drought stress and actively contribute in PGPR-induced tolerance. The study screened for and identified drought and heat tolerant PGPR that could enhance plant growth and adaptation to drought and heat stress. The potential PGPR were identified as relatives of Bacillus cereus (11MN1), B. pseudomyciodes (21MN1B), Lelliottia amnigena (33MP1), and Leclercia adecarboxylata (36MP8). A greenhouse trial showed that isolates L. amnigena 33MP1, L. adecarboxylata 36MP8, and a mixture of isolates (11MN1, 21MN1B, 33MP1, 36MP8) showed the greatest potential for alleviating the detrimental effects of concurrent drought and heat stress in maize. Quantitative reverse transcription PCR showed that induced tolerance may be achieved by modulating the catalase 2 (CAT2) and dehydrin (DHN2) stress response genes. Overall, the isolated PGPR have the potential to increase maize production, especially under drought-stricken and heat-stressed conditions, as well as reduce the need for extensive irrigation of maize crops.